Common fixed points of a countable family of multivalued quasi-nonexpansive mappings in uniformly convex Banach spaces - Bunyawat A. (Taylor and Francis Ltd., 2015)
In this paper, we introduce a one-step iterative scheme for finding a common fixed point of a countable family of multivalued quasi-nonexpansive mappings in a real uniformly convex Banach space. We establish weak and strong convergence theorems of the proposed iterative scheme under some control conditions. © 2012 Copyright Taylor and Francis Group, LLC.